Genome sequence and analysis of the tuber crop potato - Xu X. (2011)
Peruvian Ministry of Agriculture-Technical Secretariat of coordination with the CGIAR, Peruvian National Council of Science and Technology (CONCYTEC), Polish Ministry of Science and Higher Education (47/PGS/2006/01), Programa Cooperativo para el Desarrollo Tecnológico Agroalimentario y Agroindustrial del Cono Sur (PROCISUR), Project Programa Bicentenario de Ciencia y Tecnologı´a - Conicyt, PBCT - Conicyt PSD-03, Russian Foundation for Basic Research (09-04-12275)